Implementation Of Chemistry Learning Through Guided Inquiry Using Small Scale Laboratory Media On Science Process Skills - Salfiah, Salma; Hidayah, Fitria Fatichatul; Wahyuni, Endang Tri (LAVOISIER: Chemistry Education Journal, 2024)
Science process skills are very important for students to have, but their optimization is still low. It requires student-centered learning, namely guided inquiry an open sexta media small scale laboratory to assist inquiry activities in schools which are still constrained in carrying out practicums in laboratories. The purpose of this study was to analyze tha level of science process skill through open inquiry learning and guided inquiry using small scale laboratory scuta media to compare the two types of quasi-experimental research conducted at Ma’arif Karangawen High School. The design used in Noneqivalent Control Group Design. Data collection techniques namely pretest/posttest and non-test namely by observation, then tested with n-gain, normality test, homogeneity test, and hypothesis testing (t-test) and non-test data analysis. So the results of science process skill with guided inquiry learning are superior to the open inquiry learning method, indicate by the higher average value of the control class using the guided inquiry metod, namely 55,58, an increase 35,58% and n-gain value of 0,44 in the medium category. The experimental class used the open method, namely 50,15, an increase of 27,57% and an n-gain value of 0,35 in the medium category.